DEVELOPMENT PROSPECTS ICT AND E-GOVERNMENT IN UZBEKISTAN'S ECONOMY - Aman T. Кenjabaev; Mahmudzhan M. Ikramov (Статистика и экономика, 2016)
This article highlights the role and importanceof information and communication technologies (ICTs) in the economic development ofUzbekistan. The article deals with national characteristics of ICT applications and analyzes the growth rates of the economy of the republic withthe help of ICT, as well as discusses the theory and practice of application of e-government.Analyzes the shortcomings of it modern systemof "electronic government" in Uzbekistan andrecommended ways to overcome them.